Completion of isoniazid preventive therapy and factors associated with non-completion in an antiretroviral therapy-naive HIV-infected cohort in Cape Town by Tolu Oni. - Oni, Tolu (Department of Public Health and Family Medicine, 2015)
includes bibliographic references.